3D Studio Max Working Window Interface, Drawing Panel And Their Intelligence Algorithms (Eurasian Research Bulletin, 2026)
In my article mainly 3D Studio Max software worker mirror interface , main management elements and drawing (model creation ) panel opportunities illuminating Also , in the program three size models create in the process applicable main orders and from them use algorithms analysis 3D Studio Max software is used for design , architecture , animation . and computer graphics in the fields wide application because of his/her interface and functions study important is considered. In the article users for comfortable was worker environment, drawing panel elements and them practical in process application stages about scientific and practical information given.